Displacement Transformations as a Tool to Study Many-Body Localization - Serna, Pablo; Ortuño, Miguel; Somoza, Andrés M. (Frontiers in Physics, 2021)
We obtain eigenstates of interacting disorder Hamiltonians using unitary displacement transformations that rotate the state of the system. The method generates excited states if the strength of these transformations is chosen to optimize the energy, while decreasing the energy variance. We apply the method to analyse the localization properties of one-dimensional spinless fermions with short range interactions, reaching relatively large system sizes. We quantify the degree of localization through the evolution of the inverse participation ratio as a function of the energy variance.